Análisis fisicoquímicos en la implementación del proceso de potabilización y control de calidad de agua de pozo - Garzón García, Guillermo (Universidad Santiago de Cali, 2020)
Physicochemical results are presented as follow-up of the implementation in the dosage of chemical reagents (aluminum sulfate and aluminum hydroxychloride, "coagulants", calcium hypochlorite, "flocculant" anionic polyacrylamide and slaked lime) in a well water treatment plant. The optimal dosage values were obtained by jar tests in the clarification process. The implementation of water quality controls was monitored for 24 months, procedures such as cleaning, sanitation and maintenance of pumps, tanks and equipment were considered. Scope related to the improvement in 88.46% of the quality of well water was observed, with decrease in operating costs by 38.89% and the decrease in environmental impact by lowering water waste from 13,000 m3 to 2700 m3 per month.